Answer:
256
Step-by-step explanation:
A calculator works well for this.
_____
None of the minus signs are subject to the exponents (because they are not in parentheses, as (-1)^5, for example. Since there are an even number of them in the product, their product is +1 and they can be ignored.
1 to any power is still 1, so the factors (1^n) can be ignored.
After you ignore all of the things that can be ignored, your problem simplifies to ...
(2^2)(2^-3)^-2
The rules of exponents applicable to this are ...
(a^b)^c = a^(b·c)
(a^b)(a^c) = a^(b+c)
Then your product simplifies to ...
(2^2)(2^((-3)(-2)) = (2^2)(2^6)
= 2^(2+6)
= 2^8 = 256
-6x-4(-7x-13)=-58
Multiply the bracket by -4
-6x-4(-7)-4(-13)= -58
-6x+28x+52= -58
22x+52= -58
Move +52 to the other side. Sign changes from +52 to -52.
22x+52-52= -58-52
22x= -110
Divide by 22.
22/22x= -110/22
x= -5
Answer: x= -5
-2.4b = 14.4
Inverse operation
-2.4b/-2.4 = 14.4/-2.4
b = -6
Answer: b = -6
Answer:
No Solution
Explanation:
Since angle R is an obtuse angle, side r has to be the longest in length, but it isn't, so it can't form a triangle
Answer: 12 : 14 18 : 21 24 : 28 30 : 35
Step-by-step explanation:
hope these is the right answer to your question